Research on South American Leaf blight (Microcyclus ulei) of rubber in Brazil - Gasparotto L; Lima M I P M (Indian Journal of Natural Rubber Research, 1991)
South American leaf blight (SALB), caused by Microcyclus ulei, remains a problem of overriding importance of rubber (Hevea brasiliensis) cultivation in Brazil. The disease is widely distributed and is responsible for poor latex yield. Research on this disease is concentrated on epidemiology, development of resistance, disease avoidance mechanisms and chemical control.
Keywords: Brazil; Hevea brasiliensis; Microcyclus ulei; South American Leaf Blight